2023
DOI: 10.3390/v15040958
|View full text |Cite
|
Sign up to set email alerts
|

T Cells in Tick-Borne Flavivirus Encephalitis: A Review of Current Paradigms in Protection and Disease Pathology

Abstract: The family Flaviviridae is comprised of a diverse group of arthropod-borne viruses that are the etiological agents of globally relevant diseases in humans. Among these, infection with several of these flaviviruses—including West Nile virus (WNV), Zika virus (ZIKV), Japanese encephalitis virus (JEV), tick-borne encephalitis virus (TBEV), and Powassan virus (POWV)—can result in neuroinvasive disease presenting as meningitis or encephalitis. Factors contributing to the development and resolution of tick-borne fla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 161 publications
0
4
0
Order By: Relevance
“…By diffusion from capillary endothelial cells through the highly permeable blood-brain barrier [108] Studies performed on neurons and astrocytes differentiated from human neural progenitor cells (hNPCs) have shown that this cell type is permissive of TBEV infection [113].…”
Section: Via Neurons After Infection Of the Peripheral Nerves [108]mentioning
confidence: 99%
See 1 more Smart Citation
“…By diffusion from capillary endothelial cells through the highly permeable blood-brain barrier [108] Studies performed on neurons and astrocytes differentiated from human neural progenitor cells (hNPCs) have shown that this cell type is permissive of TBEV infection [113].…”
Section: Via Neurons After Infection Of the Peripheral Nerves [108]mentioning
confidence: 99%
“…During viremia, tick-borne encephalitis virus passes the blood–brain barrier (BBB) and thereby enters the central nervous system (CNS) [ 108 ]. Neurons are the primary targets of TBEV infection in the CNS, but it is important to note that the exact mode of entry into the CNS and the cell receptors are still not fully understood [ 109 , 110 ].…”
Section: Pathogenesis Of Tick-borne Encephalitis Virus Infectionmentioning
confidence: 99%
“…Recent reviews on tick-borne Borrelia spp. and TBFV have focused on getting information on the biology of infection in vertebrate hosts [ 13 , 14 ], reporting prevalence and clinical cases in human [ 15 , 16 ] and discussing diagnostic methodologies [ 17 , 18 ], the role of non-vector transmissions for TBFV [ 19 , 20 ], or on the importance of modelling TBP regarding climate change [ 21 , 22 ]. Some reviews have focused on wildlife hosts but only at a national or continental scale [ 23 , 24 ], or on reservoirs associated with flaviviruses in general, with little focus on TBFV [ 25 ].…”
Section: Introductionmentioning
confidence: 99%
“…Recent reviews on tick-borne Borrelia spp. and TBFV have focused on getting information on the biology of infection in vertebrate hosts[14,15], reporting prevalence and clinical cases in human[16,17] and discussing diagnostic methodologies[18,19], the role of non-vector transmissions for TBFV[20,21], or on the importance of modelling TBP regarding climate change[22,23]. Some reviews have focused on wildlife hosts but only at a national or continental scale[24,25], or on reservoirs associated with flaviviruses in general, with little focus on TBFV[26].…”
Section: Introductionmentioning
confidence: 99%